Functional characterization of the cell division protein MinE from the Gram-negative coccus Neisseria gonorrhoeae - Eng, Nelson F (University of Ottawa (Canada), 2007)
The Min system, comprising MinC, MinD, and MinE, is found in many Gram-negative bacterial species, including the bacillus Escherichia coli (Ec), and the coccus Neisseria gonorrhoeae (Ng). The Min proteins are important to properly initiate cell division in bacteria at the midcell. Previously, it had been considered that Min proteins were implicated in midcell site selection in only rod-shaped bacteria. Our laboratory previously identified and examined MinC and MinD from N. gonorrhoeae and discovered that these proteins were involved in cell division in N. gonorrhoeae. Since our laboratory also identified minE in N. gonorrhoeae, a coccal organism, I speculated that MinE also played a role in the cell division of round-shaped bacteria. Inactivating minENg by gene disruption failed to produce a mutant N. gonorrhoeae knockout, suggesting that minENg is an essential gene. Growth curves of N. gonorrhoeae cells overexpressing MinENg showed increased log phase growth, followed by an abrupt death phase compared to wild-type N. gonorrhoeae. While overexpression of MinENg also delayed chromosome condensation and ultimately, cell division in N. gonorrhoeae , it did not affect cell morphology or division in alternating perpendicular planes typical of N. gonorrhoeae. Our laboratory previously established that E. coli was a useful model organism to study MinENg function. Using this model, I determined that two MinENg domains (aa 12--26 and aa 57--72) were responsible for MinDNg interaction. Furthermore, by mutating five conserved MinENg residues (A18, L22, R30, K53 and E67), I discovered that the N-terminus of MinENg (aa 1--30) was essential for MinDNg binding and recruitment to the coiled subcellular architecture formed by Min proteins in E. coli. With an intact N-terminus, MinDNg localized to the coiled array and could oscillate irrespective of ATPase stimulation by MinENg. Differences in MinDNg binding to the C-terminus of MinENg (aa 31--87) were associated with differences in their ability to stimulate the ATPase activity of MinD Ng. Thus, ATPase stimulation by MinENg is dependent on the amount of interaction between MinDNg and MinENg. This property of MinENg is likely required to ensure that MinD Ng oscillation is MinENg-specific so that proper midcell site selection for cytokinesis can occur. Interestingly, I discovered that MinENg-GFP ring/coil formation did not occur unless the fusion protein was highly expressed relative to MinEEc-GFP; in addition, the MinENg-GFP superstructures do not oscillate. The domains of MinENg self-interaction included a predicted C-terminal alpha-helix (aa 39--54) and beta-sheet (aa 74--78). These domains were also important for MinDNg interaction. Disrupting MinENg/MinENg interaction caused GFP-MinDNg to primarily localize to the cell membrane and few cells showed proper MinD Ng localization (i.e. rapid MinDNg oscillation). In those cells, the MinDNg periodicity cycle was increased approximately 10-fold. Loss of MinENg self-interaction also caused some cells to filament. These results implied that proper MinDNg function was dependent on MinENg self-interaction. Therefore, it is likely that MinDNg interacts with dimerized MinENg. This is the first study that critically analyzes MinE from naturally round bacteria and its function in N. gonorrhoeae and E. coli. These studies not only enhanced the current knowledge of MinE functionality, but also provide insight into unique MinENg behaviour.
Keywords: Biology, Cell.; Biology, Microbiology.